Inclusive, Responsive, Democratic Local Government Institution and Active Citizens - Anita Marianata (Indonesian Association for Public Administration, 2019)
Reform in decentralization and village democratization can be seen in the involvement of villagers in the policy-making process, both in the economic, political and rural development fields. In the community planning process there is widespread (participatory) community involvement. The involvement of citizens in village development is one part of the development goals. Equality, justice, non-violence, tolerance, inclusiveness, transparency, accountability and responsiveness are principles that must be put forward in the village development planning process. The involvement of citizens in village development planning and budgeting aims to ensure and identify what should be the development priorities, policies, programs and activities that require budget or resources. By using a descriptive qualitative approach, this research is expected to be able to understand more deeply about inclusive and responsive democracy carried out by village government institutions and the involvement of villagers' participation. This is one of the first steps that should be taken by the village government in building democracy at the village level.